2000
DOI: 10.1046/j.1365-313x.2000.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Complex structure of a maize Myb gene promoter: functional analysis in transgenic plants

Abstract: SummaryThe maize P gene encodes a Myb-like transcription factor that regulates synthesis of red¯avonoid pigments in¯oral organs. To study the transcriptional regulation of the P gene, candidate regulatory sequences of the P1-rr gene promoter were identi®ed by Ac insertional mutagenesis and subjected to functional testing in transgenic maize plants. The results indicate that a 561 bp fragment (Pb) encompassing the transcription start site (±235 to +326) supports weak expression of a GUS reporter gene in¯oral or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 48 publications
6
68
0
Order By: Relevance
“…According to the DNA gel blot patterns, the single-copy p1 alleles, including 6 P1-rw and 9 P1-rr alleles, can be classified into six allelic types: three P1-rr types and three P1-rw types (Table 1; Figure 1, A and B). The P1-rr4B2 and P1-rw1077 allelic types have been characterized and compared previously (Lechelt et al 1989;Sidorenko et al 2000;Zhang and Peterson 2005). Representative alleles from the other four allelic types (P1-rrCFS36, P1-rr1088, P1-rwCFS302, and P1-rwCFS342, phenotypes are shown in Figure 1A) were chosen for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the DNA gel blot patterns, the single-copy p1 alleles, including 6 P1-rw and 9 P1-rr alleles, can be classified into six allelic types: three P1-rr types and three P1-rw types (Table 1; Figure 1, A and B). The P1-rr4B2 and P1-rw1077 allelic types have been characterized and compared previously (Lechelt et al 1989;Sidorenko et al 2000;Zhang and Peterson 2005). Representative alleles from the other four allelic types (P1-rrCFS36, P1-rr1088, P1-rwCFS302, and P1-rwCFS342, phenotypes are shown in Figure 1A) were chosen for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Structural comparisons of p1 alleles: Previous studies have shown that the coding regions of different p1 alleles share high sequence similarity; and DNA polymorphisms in noncoding regulatory regions other than in coding regions could be responsible for phenotypic variations of the p1 alleles (Lechelt et al 1989;Sidorenko et al 2000;Zhang and Peterson 2005). To examine sequence polymorphisms in noncoding regions of the single-copy p1 alleles studied here, we used genomic PCR with p1-specific primers to amplify both 59 and 39 noncoding regions of the P1-rr and P1-rw alleles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations